2022
DOI: 10.1007/s12369-021-00851-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Social Robots in Robot-Assisted Interventions for Social Anxiety

Abstract: Social anxiety disorder or social phobia is a condition characterized by debilitating fear and avoidance of different social situations. We provide an overview of social anxiety and evidence-based behavioural and cognitive treatment approaches for this condition. However, treatment avoidance and attrition are high in this clinical population, which calls for innovative approaches, including computer-based interventions, that could minimize barriers to treatment and enhance treatment effectiveness. After review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 254 publications
(470 reference statements)
0
22
0
Order By: Relevance
“…The incorporation of interactive social robots as social mediators, instructors, or screening agents is a work that is still in progress and there is a great interest in integrating evidence-based treatment techniques. For instance, a recent publication proposes robot-based therapeutic scenarios for social anxiety disorders to inspire future empirical work [ 20 ]. Nonetheless, further research is needed to demonstrate the reliability and consistent efficacy of such intervention protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of interactive social robots as social mediators, instructors, or screening agents is a work that is still in progress and there is a great interest in integrating evidence-based treatment techniques. For instance, a recent publication proposes robot-based therapeutic scenarios for social anxiety disorders to inspire future empirical work [ 20 ]. Nonetheless, further research is needed to demonstrate the reliability and consistent efficacy of such intervention protocols.…”
Section: Discussionmentioning
confidence: 99%
“…This discovery offers a new way for the creation of a human-computer interactive learning environment. Furthermore, the ability to converse and exchange with avatars may even be beneficial for reducing social anxiety ( Rasouli et al, 2022 ). Based on this information, it may be concluded that the use of virtual characters’ emotional support as a means of assisting students’ learning may actually contribute to the development of their social skills, such as their ability to communicate and interact with others.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study by Nomura and colleagues [54] showed the benefits of employing social robots for minimising social tensions and anxieties, describing that participants with higher social anxiety tended to feel less anxious and demonstrate lower tensions when knowing that they would interact with robots in opposition to humans. In fact, a recent paper [55] stresses the benefits of employing social robots as interventions for social anxiety, stating that these could complement the support provided by clinicians. The authors explain that social robots could support people to get into therapy and maximize the effectiveness of the therapy by increasing the patients' engagement and continuing the support outside the therapy session.…”
Section: Social Robots For Well Beingmentioning
confidence: 99%